Construction of splines curves and surfaces using MATLAB - Plukienė, Danutė; Plukas, Kostas (Lietuvos matematikos rinkinys, 2003)
Theoretical and practical aspects of construction splines curves and surfaces with MATLAB are discussed in this paper.